A Theoretical and Empirical Investigation on the Operating Performance of UK Buyout Flotations - Wang, Shaomeng (2012)
The UK has the largest and most mature buyout market in Europe. Regarding the buyout exit, Flotation has been one of the most favourable routes. This dissertation evaluates the post-issue operating performance of UK buyout companies by using a hand-collected dataset of 75 buyouts and 75 matched non-buyouts, which went public during the period between 2000 and 2007. In particular, the performance is considered by profitability, efficiency, sales and employment, from one year before Flotation to five years after Flotation. We find that although both buyouts and non-buyouts exhibit deterioration in profitability after Flotation, their post-issue efficiency, sales and employment all demonstrate improvements. Furthermore, after Flotation, buyouts outperform non-buyouts in profitability, but underperform in sales and employment. There is no significant difference in post-issue efficiency changes between the two groups. Compared with the performance before Flotation, buyouts perform more sustainable and stable than non-buyouts after the issue. We go on to examine the determinants of performance changes. The regression analyses report weak evidence on the positive impact of buyout structures, particularly in efficiency and sales. Even though VC backing plays a positive role, buyout longevity and firm age may negatively related with the performance. Moreover, gearing has a positive association with profitability, but a negative association with sales. In addition, firms coming from high technology industries or floating on AIM may have better performance, while firms floating during hot market periods may perform worse than those floating during normal periods.